1986
DOI: 10.1093/oxfordjournals.aje.a114283
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of Dental Enamel Among Competitive Swimmers at a Gas-Chlorinated SWLMMTNG Pool

Abstract: In September 1982, two Charlottesville, Virginia, residents were found by their dentists to have general erosion of dental enamel consistent with exposure to acid. Both patients were competitive swimmers at the same private club pool. No other common exposure could be determined. An epidemiologic survey was made of 747 club members. Symptoms compatible with dental enamel erosion were reported by 3% of nonswimmers (9/295), 12% of swimmers who were not members of the swim team (46/393), and 39% of swim team memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 0 publications
2
40
0
9
Order By: Relevance
“…Unadjusted odds do not eliminate the influence of other factors that an individual has in the calculation, but other authors have found that creating adjusted odds makes little difference to the odds ratio and it is a more complicated calculation [Centerwall et al, 1986]. When commenting on the odds ratios each control group needs to be considered individually, and the risk of each factor causing erosion in a caries-free individual and a caries-active individual calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unadjusted odds do not eliminate the influence of other factors that an individual has in the calculation, but other authors have found that creating adjusted odds makes little difference to the odds ratio and it is a more complicated calculation [Centerwall et al, 1986]. When commenting on the odds ratios each control group needs to be considered individually, and the risk of each factor causing erosion in a caries-free individual and a caries-active individual calculated.…”
Section: Discussionmentioning
confidence: 99%
“…The chi-squared test was used for differences in salivary buffering capacity. Unadjusted odds ratios were then calculated for the various factors in order to make some assessment of the risk of developing erosion from each individual factor [Centerwall et al, 1986]. Each factor that had been examined in association with erosion was taken and the odds ratios calculated at the 95% confidence level, for the erosion study group compared with each of the control groups.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…Employees in the chemical industry or professional wine tasters have a higher risk of suffering erosions due to the increased acid-tooth contact . Tooth erosion associated with professional athletes or excessive exercise has also been reported occasionally [Centerwall et al, 1986]. Excessive exposure to water or sport drinks with low pH, or the increased gastrooesophageal reflux resulting from strenuous exercise may be responsible for the sport-induced erosion [Centerwall et al, 1986].…”
Section: Risk Factors and Aetiologymentioning
confidence: 99%
“…35,36 Health and safety laws have probably reduced the risk of environmental erosion although it should not be ignored as a possible aetiological factor. Environmental erosion predominantly affects the labial surfaces of the maxillary and mandibular incisors.…”
Section: Environmental Erosionmentioning
confidence: 99%